Prospects of Solar Power Satellite in Bangladesh (Global Journals of Research in Engineering, 2013)
This paper is a quick study overview of the space solar power, its current status and the prospects of the implementation of Solar Power satellite (SPS) in Bangladesh. Collecting energy in space and to redirect it to Earth provides significant advantages in the continuity of supply with very little environmental impact. But, its development represents many challenges both technically and economically. Bangladesh is very close to launch its first communication satellite in space. It is proposed in this paper to integrate SPS module with that Satellite for providing the long time solution of the power crisis.